INCREASE TEACHER CREATIVITY AND COMPETENCE WITH INTERACTIVE LEARNING MEDIA THROUGH THE WORDWALL APPLICATION AT SD NEGERI 1 SEGEDONG - Imran, Imran; Ramadhan, Iwan; Prancisca, Stella; Zatalini, Adhalia; Astari, Zuri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This research aims to increase teacher creativity and competence through interactive learning media using the Wordwall application at SD Negeri 1 Segedong. The background of this research is the importance of the role of teachers in delivering quality learning to achieve educational progress. Analysis of the situation shows that technological developments affect learning methods that must be adapted to the needs of the times. The problem faced is the lack of creativity in the learning process which can affect students' interest in learning. The proposed solution is training in the use of the Wordwall application to create interactive and engaging learning. The results showed that the use of the Wordwall application can increase teacher creativity and student learning interest. In conclusion, the implementation of interactive learning media through Wordwall can make a positive contribution to improving the quality of learning in schools.